If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 3 = 2x + 0 Reorder the terms: 3 + -1x = 2x + 0 Reorder the terms: 3 + -1x = 0 + 2x Remove the zero: 3 + -1x = 2x Solving 3 + -1x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + -1x + -2x = 2x + -2x Combine like terms: -1x + -2x = -3x 3 + -3x = 2x + -2x Combine like terms: 2x + -2x = 0 3 + -3x = 0 Add '-3' to each side of the equation. 3 + -3 + -3x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = 0 + -3 -3x = 0 + -3 Combine like terms: 0 + -3 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| x/8+9=x/8 | | 4.43x+3.41y=50.10 | | y=33(4)-0.5 | | 10(h+1)=3(2h+4)-2(-2h+1) | | 9.99+1.25*7= | | y=33(2)-0.5 | | 24x+1=4 | | -2-(3/4x)=10 | | 9.99+1.25*6= | | 3x+6=-2x+41 | | 3r+18/12=4r-24/4 | | 9.99+1.25*5= | | 9=-3/5x | | 9.99+1.25*4= | | -7/4=p/28 | | 7/2+12=6+5/2 | | 7/2+12=6+5/2 | | 9.99+1.25*3= | | 31=x+x+(x-1) | | X^3+x^2+9x+9=0 | | 9.99+1.25*2= | | 7x^2-40x-12x=0 | | a-(-6)=12 | | -12*(-55)*0= | | 8x+7=90 | | 5-x=(1/2x)+4 | | 4z+3z-6-7z=6 | | 7x=2x+1 | | -31+(-28)-(-14)-16= | | 8f-4=6f+26 | | 3y/x | | 3a+4b=(1-2c)/d |